Cardiac effects of amiselimod compared with fingolimod and placebo: results of a randomised, parallel‐group, phase I study in healthy subjects. (19th January 2017) - Harada, Tomohiko; Wilbraham, Darren; de La Borderie, Guillemette; Inoue, Shinsuke; Bush, Jim; Camm, A. John
Abstract : Aim: Amiselimod (MT‐1303) is a selective sphingosine 1‐phosphate 1 (S1P1 ) receptor modulator which is currently being developed for the treatment of various autoimmune diseases. Unlike some other S1P receptor modulators, amiselimod seemed to show a favourable cardiac safety profile in preclinical, phase I and II studies. The aim of the current study was to characterize the cardiac effects of amiselimod by directly comparing it with fingolimod and placebo. Methods: A total of 81 healthy subjects aged 18–55 years were equally randomized to receive amiselimod 0.4 mg, amiselimod 0.8 mg, placebo or fingolimod 0.5 mg once daily for 28 days. The chronotropic/dromotropic and inotropic effects were evaluated using intensive Holter electrocardiogram and echocardiography. Results: Unlike fingolimod, neither amiselimod dose exerted acute (1–6 h) negative chronotropic effects on Days 1 and 2. The lowest nadir mean hourly heart rate was observed on Day 14 in the amiselimod 0.4 mg group (least squares mean difference: −4.40 bpm, 95% confidence interval −7.15, −1.66) and Day 7 in the 0.8 mg group [−3.85 bpm (−6.58, −1.11)] compared with placebo, but these changes were smaller than those with fingolimod on Day 1 [−6.49 bpm (−8.95, −4.02)]. No clinically significant bradyarrhythmia or cardiac functional abnormalities were observed in either amiselimod group. Both amiselimod doses were well tolerated and no serious adverse events were reported. Fingolimod was also generally well tolerated, although one subject was withdrawn owing to highly frequent 2:1 atrioventricular blocks on Day 1. Conclusion: The study demonstrated a more favourable cardiac safety profile for amiselimod than fingolimod when administered over 28 days in healthy subjects.